HOW INTEREST RATES INFLUENCE PRICING AND TRADE CREDIT POLICIES: A COMPREHENSIVE STUDY - Leclerc , Olivia Marie; Wong, Alexander James (Ayden International Journal of Applied Economics, Finance and Accounting, 2025)
This study investigates the impact of trade credit on the effectiveness of monetary policy transmission, addressing the empirical observation that trade credit tends to mitigate the effects of central bank actions. To elucidate this phenomenon, we develop a partial equilibrium model that incorporates third-degree price discrimination and menu costs. Our primary finding reveals that optimizing credit terms and product prices yields minimal net present value (NPV) gains compared to the minute menu costs associated with short-term interest rate adjustments during low-inflation periods. Consequently, credit terms and product prices remain relatively stable over time, in alignment with empirical evidence presented by Ng, Smith, Smith (1999), and Mateut (2005). Furthermore, our model provides insights into the Meltzer (1960) hypothesis, suggesting that trade credit experiences less volatility than bank credit in the context of monetary policy transmission. This implies that firms strategically set trade credit terms to maximize NPV while considering menu costs, thereby rationalizing certain credit channel-related empirical phenomena. The paper also explores parallels between trade credit dynamics and exchange rate pass-throughs, shedding light on the effectiveness of monetary easing during a pandemic. These findings contribute to a deeper understanding of the intricate relationship between trade credit and monetary policy, with potential implications for policy design and implementation